Posted by **Satrianna** on Saturday, January 19, 2013 at 2:57pm.

3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-4

I got

3x^3+2x^2-12x+8 / (x-1)(2x-3) (x-4)

Is this right please show your steps so I can understand!

Thanks I greatly appreciate your help!

## Answer this Question

## Related Questions

- math - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-4 I got 3x^3+2x^...
- algebra - Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6...
- math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...
- Algebra - What is the side length of a square with an area of 144x²? A.12 B.12x ...
- Algebra. Please check my answers - Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42...
- algebra - find a third degree polynomial equation with coefficients that has ...
- math - simplify and state any restrictions: 1. x+3/x^2+11x+24 - 2x+10/x^2+11x+30...
- Algebra - I'm not sure how to factor 3x^3-12x^2+3x. I tried separatring the 3x ...
- Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...
- Urgent Math please check - Very Important I can get someone to check these for ...

More Related Questions